Glioma-Associated Sialoglycans Drive the Immune Suppressive Phenotype and Function of Myeloid Cells - Lenneke A. M. Cornelissen; Kim C. M. Santegoets; Esther D. Kers-Rebel; Sandra A. J. F. H. Bossmann; Mark Ter Laan; Daniel Granado; Gosse J. Adema (MDPI AG, 2024)
The tumor microenvironment of glioblastoma IDH-wildtype is highly immune suppressive and is characterized by a strong component of myeloid-derived suppressor cells (MDSCs). To interfere with the immune suppressive functions of MDSCs, a comprehensive understanding on how MDSCs acquire their suppressive phenotype is essential. Previously, we and others have shown a distinct Sialic acid-binding immunoglobulin-like lectin (Siglec) receptor expression profile for MDSCs in glioblastoma. Siglec receptors can transmit inhibitory signals comparable to PD-1 and are suggested to act as glyco-immune checkpoints. Here, we investigated how glioma specific Siglec-sialic acid interactions influence myeloid immune suppressive functions. Co-culturing monocytes with glioblastoma cells induced CD163 expression on the monocytes. Upon desialylation of the glioblastoma cells, this induction of CD163 was hampered, and furthermore, the monocytes were now able to secrete higher amounts of IL-6 and TNFα compared to fully sialylated glioblastoma cells. Additionally, Siglec-specific triggering using anti-Siglec-7 or Siglec-9 antibodies displayed a decreased TNFα secretion by the monocytes, validating the role of the Siglec-Sialic axis in the co-culture experiments. Together, our results demonstrate that glioblastoma cells induce a myeloid immune-suppressive phenotype that could be partly rescued by lowering the glioblastoma-associated sialic acid levels. This manuscript supports further research of the Siglec-Sialic acid axis in the context of glioblastoma and its potential to improve clinical outcome.